A mini review of designed mesoporous materials for energy-storage applications: from electric double-layer capacitors to hybrid supercapacitors. Issue 15 (29th March 2016) - Lim, Eunho; Jo, Changshin; Lee, Jinwoo
Abstract : In recent years, porous materials have attracted significant attention in various research fields because of their structural merits. Abstract : In recent years, porous materials have attracted significant attention in various research fields because of their structural merits. In particular, well-designed mesoporous structures with two- or three-dimensionally interconnected pores have been recognized as electrode materials of particular interest for achieving high-performance electrochemical capacitors (ECs). In this mini review, recent progress in the design of mesoporous electrode materials for ECs, from electric double-layer capacitors (EDLCs) and pseudocapacitors (PCs) to hybrid supercapacitors (HSCs), and research challenges for the development of new mesoporous electrode materials has been discussed.